Splice-site mutation enhances the efficiency of CRISPR-mediated gene knockout and new germplasm creation in fish - Zhen Xu; Ma Zhuo; Leihui Wang; Shuo Yan; Shiyi Zhang; Ying Chen; Guang Xu; Chenxu Wang; Wenjing Tao; Deshou Wang (Aquaculture Reports, 2025)
The knockout efficiency of the CRISPR/Cas9 system largely relies on the frameshift mutation caused by random insertions or deletions at target site of coding DNA sequence (CDS). Splice site (SS) mutations result in mRNA mis-splicing, making gRNAs targeting SS more likely to produce null mutations and thereby enhancing CRISPR efficiency. In this study, gRNAs were designed to target both the CDS and SS of tyrb, hps4, hps5, chrd, eda, fgfr1a, fgf8a and bmp2b in tilapia. Remarkably higher null mutation rate was observed in F0 mutants injected with gRNAs targeting SS compared to those targeting CDS. By transcriptome analysis, E2 skipping, I5 retention and I7 retention were observed in tyrb I2 5’SS, hps4 I5 3’SS and hps5 I7 5’SS mutation, respectively. Furthermore, the phenotype rates were counted for F0 of tyrb (53.8 %/6.9 %), hps5 (78.4 %/0 %) and chrd (49.38 %/16.18 %), and remarkably higher phenotype rates were observed in fish injected gRNAs targeting SS than those targeting CDS. For tyrb and hps5, around 30 % of F0 fish displayed the albino phenotypes as observed in homozygous mutants when targeting SS, whereas those targeting CDS exhibited only a partial reduction of pigmented melanophores on their body surfaces. Mutations in any of the four bases (“NNGT” or “AGNN”) at the exon-intron boundary resulted in mRNA mis-splicing. The CRISPR/cas9 mediated SS mutation was most efficient when the target was selected to produce a DSB within 4 bp flanking the exon-intron boundary. These results demonstrated that gRNAs targeting SS provided an alternative and effective option for gene mutation and new germplasm creation in fish.